The Influence of Personal Brand Trust on Community Leaders Who Are Also Entre-preneurs in DKI Jakarta on Overall Brand Equity - Riyandi Riyandi; Nuri Wulandari (Indonesia Banking School, 2022)
This study aimed to investigate Personal Brand Trust in Famous Entrepreneurs in DKI Jakarta and its im-pact to Brand Awareness, Perceived Quality, Brand Loyalty and Overall Brand Equity. By Quantitatif Analysis through a questionnaire, the sample in this study were taken by using the data collection method called random sampling. The number of samples that used were 159 respondents. The data obtained were analyzed by using PLS analysis technique (Partial Least Square) through the PLS software. The results showed that Personal Brand Trust directly and positively related to Brand Awareness, Brand Loyalty and Perceived Quality. Furthermore, Brand Awareness & Brand Loyalty has positive effect on Overall Brand Equity.The result of this research also shows that Perceived Quality does not have a positive effect on Overall Brand Equity.